Development of Qr-Code Media-Based Modules in Constructing Learning to Increase Learning Motivation - Kandiri, Kandiri; Nurwahidin, Muhammad; Aransyah, Ade; Purmadi, Ary (UNDIKMA, 2025)
Education plays an important role in preparing the younger generation to face the challenges of the 21st century. One innovation in education is the development of QR-Code media-based modules to increase student learning motivation. QR-Code technology allows teachers to present learning materials in an interactive and interesting way, thus increasing student involvement in the learning process. In addition, QR-Code-based modules also allow easy and practical access for students in learning materials inside and outside the classroom. By utilizing this digital technology, teachers can provide a more engaging and effective learning experience for students, thus supporting the development of 21st century skills required in an ever-evolving world. Therefore, it is important for educators to continue to develop and utilize technology in providing innovative and relevant learning resources for learners.